Pendidikan Kesehatan Reproduksi Remaja Bagi Orang Tua Komunitas Pekerja Migran Asal Kampung Pandan, Malaysia: Adolescent Reproductive Health Education for Parents in the Migrant Worker Community from Kampung Pandan, Malaysia - Yuliani, Anita; Fatmawati, Ariani; Teesen, Gabriele Stefhany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The